1993
DOI: 10.1111/j.1574-6976.1993.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in elucidation of biological corrinoid functions

Abstract: Eleven adenosylcorrinoid-dependent rearrangements and elimination reactions have been described during the last four decades of vitamin B12 research. In contrast, only the cobamide-dependent methionine synthase was well established as a corrinoid-dependent methyl transfer reaction. yet, investigations during the last few years revealed nine additional corrinoid-dependent methyltransferases. Many of these reactions are catalyzed by bacteria which possess a distinct C1 metabolism. Notably acetogenic and methanog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 131 publications
1
19
0
Order By: Relevance
“…It is clear that the transfer of methyl groups from methylcobalamin to arsenic over and above that of nonenzymatic controls was demonstrated (175). Methylcobalamin has been increasingly implicated in a range of methylation reactions in addition to its well-known role in methionine biosynthesis (94,143,226).…”
Section: Role Of Anaerobic Microorganismsmentioning
confidence: 99%
“…It is clear that the transfer of methyl groups from methylcobalamin to arsenic over and above that of nonenzymatic controls was demonstrated (175). Methylcobalamin has been increasingly implicated in a range of methylation reactions in addition to its well-known role in methionine biosynthesis (94,143,226).…”
Section: Role Of Anaerobic Microorganismsmentioning
confidence: 99%
“…Other modifications including removal of hydroxyl, methoxyl, amino, and acyl groups are also being studied (24,55,57) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The methanogenic strain excreted 80% of the B 12 compound produced into the medium without cell lysis 21) . The involvement of corrinoids in anaerobic dehalogenation has also been reported 19,26,29) . Thus, it is likely that the cobalamin compound produced endogenously by these microbial groups serves as an exogenous source of cobalamin for other microbial groups in the community.…”
Section: Discussionmentioning
confidence: 96%
“…Two major groups in anaerobic microbial ecosystems, acetogens and methanogens, possess distinct metabolisms relating to the cobalamin compound. Acetyl-coenzyme A biosynthesis in acetogenic bacteria as well as the acetate catabolism of methanogens involves sim- ilar corrinoid-dependent methyltransferases 29) . It has been reported that various acetogenic anaerobic bacteria including Acetobacterium spp.…”
Section: Discussionmentioning
confidence: 99%